The Effect of Celebrity Endorsement, Brand Image, and Social Media Exposure on Customer Purchase Decision on Electronic Products in Indonesia - Tubalawony, Jacsy (Westscience Press, 2025)
This study examines the impact of celebrity endorsement, brand image, and social media exposure on consumer purchasing decisions for electronic products in Indonesia. Using a quantitative research approach, data were collected from 200 respondents through a survey employing a Likert scale (1-5). The analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that social media exposure and celebrity endorsement significantly influence consumer purchasing decisions, while brand image does not have a significant effect. These results highlight the growing role of digital marketing and influencer endorsements in shaping consumer behavior in Indonesia. The study provides valuable insights for businesses, emphasizing the need for effective social media strategies and celebrity partnerships to enhance marketing effectiveness.